Las Tres Alianzas (The Three Alliances): Original song by Uri Guevara Lopez (Waslala, Nicaragua) - International Center for Tropical Agriculture (2016)
Inspired by the initiative led by the CGIAR Research Program on Integrated Systems for the Humid Tropics (Humidtropics) through CIAT, to establish the Territorial Learning Alliances in the coffee, cocoa, and mixed staple crop-livestock systems in Nicaragua, members of the territorial organization APROMUWA share their experience as participants in this Alliance through a song.